Bidirectional all-optical switches based on highly nonlinear optical fibers. (11th July 2017) - Liu, Wenjun; Yang, Chunyu; Liu, Mengli; Yu, Weitian; Zhang, Yujia; Lei, Ming; Wei, Zhiyi
Abstract: All-optical switches have become one of the research focuses of nonlinear optics due to their fast switching speed. They have been applied in such fields as ultrafast optics, all-optical communication and all-optical networks. In this paper, based on symbolic computation, bidirectional all-optical switches are presented using analytic two-soliton solutions. Various types of soliton interactions are analyzed through choosing the different parameters of high-order dispersion and nonlinearity. Results indicate that bidirectional all-optical switches can be effectively achieved using highly nonlinear optical fibers.